Technology of manufacturing copper and bronze tools of the Petrovka Culture of the Southern Trans-Urals and Middle Tobol region - Degtyareva A.D. (Вестник археологии, антропологии и этнографии)
The article presents the results of metallographic analysis of the Petrovka Culture tools from the southern Trans-Urals and Middle Tobol River region of the 19th–18th centuries BC (47 items). A certain correlation has been determined between the functional purpose of an item, the type of raw material, and the tool manufacturing scheme. The tools were mainly made of copper contaminated with impurities, obtained from oxide-carbonate ores with the addition of chalcocite-covellite minerals. A butted axe, sickles, knives with handles, tanged chisels, hooks, and some awls were made of copper, both by casting in a mold with subsequent finishing and by forming forging. Copper tools obtained by casting often had casting defects — shrinkage cracks and warping of the metal.In most cases, the tools were finished either in the regime of incomplete hot forging at 300–500°C, or hot forging at 600–800°C and pre-melting temperatures of 900–1000°C. During the Petrovka period, tin and tin-arsenic bronze started being used for manufacturing adzes, chisels, handled knives, the majority of awls, needles, spearheads, and arrows. More progressive types of alloys in terms of fluidity, filling mold without defects in the form of lowalloy tin and tin-arsenic bronzes (Sn up to 7%, As up to 4%) came from related tribes of the Petrovka Culture of Saryarka, possibly from the Petropavlovsk Ishim region. The resulting castings were of high quality with smooth surface without metal warping defects. Subsequent finishing was carried out by selecting optimal heat treatment regimes mainly at 600–800°C or 900–1000°C, as well as using incomplete hot forging at 300–500°C. The hardness of the tools finished by forging with heating significantly exceeded the microhardness of the processed copper by 1.5–2 times.